Extending the Quasidifferential Framework: From Fixed-Key to Expected Differential Probability - Boura, Christina; Derbez, Patrick; Germon, Baptiste (IACR Transactions on Symmetric Cryptology, 2025)
Beyne and Rijmen proposed in 2022 a systematic and generic framework to study the fixed-key probability of differential characteristics. One of the main challenges for implementing this framework is the ability to efficiently handle very large quasidifferential transition matrices (QDTMs) for big (e.g. 8-bit) S-boxes. Our first contribution is a new MILP model capable of efficiently representing such matrices, by exploiting the inherent block structure of these objects. We then propose two extensions to the original framework. First, we demonstrate how to adapt the framework to the related-key setting. Next, we present a novel approach to compute the average expected probability of a differential characteristic that takes the key schedule into account. This method, applicable to both linear and non-linear key schedules, works in both the single-key and related-key settings. Furthermore, it provides a faster way to verify the validity of characteristics compared to computing the fixed-key probability. Using these extensions and our MILP model, we analyze various (related-key) differential characteristics from the literature. First, we prove the validity of several optimal related-key differential characteristics of AES. Next, we show that this approach permits to obtain more precise results than methods relying on key constraints for SKINNY. Finally, we examine the validity of a differential distinguisher used in two differential meet-in-the-middle attacks on SKINNY-128, demonstrating that its probability is significantly higher than initially estimated.